2010
DOI: 10.1074/mcp.m900327-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of the Penicillin Producer Penicillium chrysogenum

Abstract: Proteomics is a powerful tool to understand the molecular mechanisms causing the production of high penicillin titers by industrial strains of the filamentous fungus Penicillium chrysogenum as the result of strain improvement programs. Penicillin biosynthesis is an excellent model system for many other bioactive microbial metabolites. The recent publication of the P. chrysogenum genome has established the basis to understand the molecular processes underlying penicillin overproduction. We report here the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 64 publications
5
84
0
7
Order By: Relevance
“…Penicillium sp. represents an ideal microbial cell factory for the expression of a multitude of genes, originating also from non-fungal species [20], as protein processing and maturation is similar to higher eukaryotes [44, 45]. Taking into account the recent approaches for “humanizing” the glycosylation profile (as one of the most common post-translational modifications) in filamentous fungi [27], the fungal expression system presented in this study could be further refined in the future for the expression of human therapeutic proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Penicillium sp. represents an ideal microbial cell factory for the expression of a multitude of genes, originating also from non-fungal species [20], as protein processing and maturation is similar to higher eukaryotes [44, 45]. Taking into account the recent approaches for “humanizing” the glycosylation profile (as one of the most common post-translational modifications) in filamentous fungi [27], the fungal expression system presented in this study could be further refined in the future for the expression of human therapeutic proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Our SILAC-based LC-MS/MS study showed the average up-regulation to 1.85 fold for protein S100A11, down-regulation to 0.10 fold for WASL and 0.25 fold for PPP1R9B. In order to validate the protein level alteration we performed the semi-quantitative RT-PCR as a standard method to evaluate the transcription level of these proteins [13]. We observed the average of 1.75 and 2.1 fold over-expression of S100A11 in mRNA level in MDA-MB-231-ShA and MDA-MB-231-ShB respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Upon completion of the cycling steps, a final extension at 72°C for 5 min was done for all of the reactions and then the reactions were stored at 4°C. The bands obtained after electrophoresis were quantified by densitometry and their intensities were normalized to that provided by the GAPDH (Glyceraldehyde 3-phosphate dehydrogenase) band (relative integral optical density (IOD)) as described before [13]. The average intensity value of the transcripts obtained from the negative control cells were set to 100%.…”
Section: Methodsmentioning
confidence: 99%
“…Focusing of proteins (using BioRad IEF instrument), equilibration of the focused IPG strips and the 12.5% SDS-PAGE for the second dimension (carried out in an Ettan Dalt Six apparatus (GE Healthcare)) were performed as previously described [51]. Briefly, proteins were focused at 20°C according to the following program: 1 h, 0 V and 12 h, 30 V (rehydration); 30-min gradient to 10,000 V; up to 9 h, 10,000 V until 85 kV-h.…”
Section: Methodsmentioning
confidence: 99%